Neonatal Chlamydial Conjunctivitis - Monteiro, Nathalia da Cruz Assad; Fernandes, Regina Celia de Souza Campos; Medina-Acosta, Enrique (Brazilian Journal of Case Reports, 2024)
Infection with Chlamydia trachomatis (CT) during pregnancy can result in serious outcomes, including miscarriage, stillbirth, low birth weight, prematurity, neonatal conjunctivitis, and neonatal pneumonia. Despite these risks, routine screening for CT during pregnancy remains infrequent, limiting the opportunity for timely intervention. This report describes a case of neonatal conjunctivitis due to CT in a 9-day-old infant born vaginally to a 15-year-old primigravida. The infant was presented with purulent discharge, eyelid edema, and pustules on the face and neck. The mother had significant risk factors, including adolescence, multiple sexual partners, and untreated vaginal discharge during pregnancy. The conjunctivitis appeared five days postpartum, with a diagnosis confirmed via real-time PCR from conjunctival scrapings. Treatment with intravenous oxacillin, ceftriaxone, and clarithromycin led to full recovery without the development of pneumonia. This case underscores the need to identify maternal risk factors, such as adolescent age, multiple sexual partners, and untreated vaginal discharge during pregnancy, and highlights the importance of enhancing prenatal screening and implementing routine STI testing to prevent neonatal complications.